Nodulaiion, biomass production, nutrient accumulation, carbon : nitrogen ratio and decomposition rate of various green manuring crops in submerged rice (Oryza sativa) soil - KUMAR, AJAY; MAHAPATRA, B S; MISRA, ALABHYA; PATRO, H K; SINGH, S P (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during the kharif season of 2001 and 2002 at Pantnagar, Uttarakhand to study nodulation, biomass production, nutrient accumulation, C:N ratio and decomposition rate of four widely grown green manure crops, viz Crotalaria juncea L., Sesbania cannabiita (Retz.) Pers, Sesbania rostrata and Vigna unguiculata (L.) Walp) in silty clay loam soil, slightly alkaline in reaction (pH 7.3), medium in organic carbon (0.604%), low in available N (238.0 kg1 ha), medium in available P (19.9 kg/ha), and K (150 kg/ha). These crops recorded significant variations innodulesl plant (1 2.5 - 56.5), fresh and dry weight (32-263 rng/plant), green (9.4-34.3 tonnesiha) and dry biomass production (2.1-6.8 tonnesiha). Sesbania cannabina at 60 days gave maximum nodules /plant (56) and nodules fresh weight (606 mglplant) and nodule dry weight (263 mglplant). While Crotalaria juncea at 60 days gave maximum green biomass (34.3 tonnesl ha) and dry biomass (6.8 tonnesiha). Nitrogen content in all green manuring crops decreased with advancement in age. However potassium content (1.74 - 2.05 %) continued to increase with age of crops. The C: N ratio widened (13.8 - 19.0) with advancement in age and the ratio narrowed with the advancement of time of their incorporation for decomposition. After 30 days of incorporation decomposition percentage was higher for 30 days old crop followed by 45 and 60 days old crop.